PENGARUH PERAN ORANG TUA DAN FASILITAS BELAJAR DALAM PEMBELAJARAN DARING TERHADAP HASIL BELAJAR TEMATIK PESERTA DIDIK KELAS IV SD NEGERI - Dian Apriansyah; Deviyanti Pangestu; Yulita Dwi Lestari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
The problem in this research is the low thematic learning outcomes of fourth grade elementary school students in Cluster 1 Gadingrejo, Gadingrejo District. The purpose of this study was to analyze and describe the positive and significant influence between the role of parents and learning facilities in online learning with thematic learning outcomes. The type of research was ex-post facto correlation with a quantitative approach. The research population were 144 students and the sample was 62 students with probability sampling techniques. The data collection instruments in the form of a questionnaire used a Likert scale. Data analysis used multiple linear regression analysis and the obtained Fcount (40) > Ftab (3.14) with a significance of 0.05 ≤ 0.05 and a contribution of 56%. The results of this research found that there was a positive and significant influence between the role of parents and learning facilities in online learning on the students' thematic learning outcomes.